2018
DOI: 10.1021/acsomega.8b01822
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Assembly of l-Phenylalanine-Terminated Bolaamphiphile with Porphyrin Show Tunable Nanostructures and Photocatalytic Properties

Abstract: Demands related to clean energy and environmental protection promote the development of novel supramolecular assemblies for photocatalysis. Because of the distinctive aggregation behaviors, bolaamphiphiles with two hydrophilic end groups could be theoretically the right candidates for the fabrication of high-performance photocatalysis. However, photocatalytic applications based on bolaamphiphilic assemblies were still rarely investigated. Especially, the relationship between diverse assembled nanostructures an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 64 publications
0
16
0
Order By: Relevance
“…However, different nanostructuring of TAPA‐OPE‐mix and TAPA‐OPE‐gly polymers can be attributed to the asymmetric and symmetric side‐chain substitutions on OPE bola‐amphiphilic struts, respectively . Here, tuning in the morphology of materials is noteworthy and indeed a crucial factor for catalytic performances by the fact that nanotape structures provide more exposed catalytic surface compared with irregular spherical morphologies . More importantly, tuning of the morphology in CMP materials by subtle variation in substitutions is yet to be realized.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, different nanostructuring of TAPA‐OPE‐mix and TAPA‐OPE‐gly polymers can be attributed to the asymmetric and symmetric side‐chain substitutions on OPE bola‐amphiphilic struts, respectively . Here, tuning in the morphology of materials is noteworthy and indeed a crucial factor for catalytic performances by the fact that nanotape structures provide more exposed catalytic surface compared with irregular spherical morphologies . More importantly, tuning of the morphology in CMP materials by subtle variation in substitutions is yet to be realized.…”
Section: Resultsmentioning
confidence: 99%
“…[29,58] Here, tuning in the morphology of materials is noteworthy and indeed ac rucial factor for catalytic performances by the fact that nanotapes tructures provide more exposed catalytic surfacec ompared with irregular spherical morphologies. [56,57] More importantly,t uning of the morphologyi nC MP materials by subtle variation in substitutions is yet to be realized. UV/Visa bsorption spectra of TAPA-OPE-mix and TAPA-OPE-gly in the solid state revealed that both CMPs exhibit broad absorbance in the range 250-600nm( Figure S8, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Porphyrin assemblies are widespread in nature, where they are engaged in essential processes, such as efficient transport or storage of oxygen through the blood plasma or electron transfer in photosynthesis. Inspired by the diverse self-assembly motifs in nature, researchers have constructed and applied synthetic porphyrin systems in a variety of applicative fields, ranging from photocatalysis to sensors and material science [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Indeed, the choice of porphyrin-based building blocks to organize supramolecular systems is extremely advantageous for several reasons: (i) their chemical versatility supported by well-established synthetic methodologies; (ii) their distinctive optical features; and (iii) their invaluable photophysical and photochemical properties that enhance the assembled materials, with obvious impacts on the performance in technological applications.…”
Section: Introductionmentioning
confidence: 99%